Selective utilization of legal avenues of assistance by women on the Caribbean Island of St Kitts in the British Leewards - Maze, Brian Lawrence (University Microfilms International Ann ArbourUS, 1985)
Identifies 5 reasons why women selectively use the law in St Kitts and the factors involved in the decision process to use or not to use the established legal system. Discusses the alternative informal system that the women use to resolve conflict and bring about social control. Briefly provides geographical, historical, demographical, and cultural background information on St Kitts and reviews the literature on ethnolegal research with special reference to the Caribbean.